A Kecemasan Ibu Hamil dalam Melakukan Antenatal Care di Masa Pandemi Covid-19: Tinjauan Pustaka: Kecemasan Ibu Hamil Di Masa Pandemi Covid-19 : A Literature Review - Wiji Astuti; Muhammad Syamsu Hidayat (Journal of Health (JoH), 2023)
Corona Virus Disease (Covid-19) is a condition that causes illness and death. As of 25 October 2022, it was stated that there were 6.472.664 total confirmed cases and 158.454 deaths in Indonesia. Pregnant women are a high-risk population for Covid-19 infection. But, a pregnant woman might be hesitant to attend a health center to monitor her pregnancy for fear of contracting Covid-19. This problem decreased the number of pregnant women in Indonesia who visited health services. This research study aims to examine the anxiety issues experienced by pregnant women during the Covid-19 pandemic. This article's methodology is based on an exhaustive search of numerous databases, including PubMed, Scopus, Google Scholar, and the official website. Articles are chosen based on criteria like free full text, open access, and publication date beyond 2020. The systematic search produced a total of 1238 articles, with 9 articles meeting the inclusion criteria. This research study concludes that pregnant women constitute a high-risk population during the Covid-19 pandemic. Pregnant women were known to feel anxiety in the majority. These psychiatric diseases offer risks to the fetus, including prenatal development impairment, early delivery, and low birth weight. Pregnant women require social assistance to lessen their fear during the Covid-19 pandemic and to increase their compliance with Ante Natal Care in an effort to discover pregnancy issues early, so that mothers and infants may be anticipated to be healthy and safe. Keywords: Pregnant, Anxiety, Covid- 19